Proportion of depression and associated factors among HIV-positive youth attending antiretroviral therapy clinics at public hospitals in Gamo and Ari zones, South Ethiopia: A facility-based cross-sectional study - Temesgen Mohammed Toma; Abraham Anbesie Sapo; Habtamu Wana Wada; Kassahun Tamene Andarige; Rahel Abera Alula; Fasika Merid Malimo; Habtamu Samuel Goda; Mintesinot Melka Gujo; Agune Ashole Alto; Tamirat Gezahegn Guyo (PLoS ONE, 2025)
Background Even though the co-occurrence of Human Immune-Deficiency Virus/Acquired Immune-Deficiency Syndrome (HIV/AIDS) and depression is the main cause of morbidity and mortality in youth living with HIV/AIDS, in Ethiopia, there is a scarcity of evidence on depression and associated factors. Hence, this study aimed at the assessment of depression and associated factors among HIV-positive youth attending antiretroviral therapy (ART) clinics at public hospitals in Gamo and Ari Zones, South Ethiopia. Method A facility-based cross-sectional study was conducted from March 1, 2024, to April 30, 2024, among HIV-positive youth attending ART clinics at public hospitals in Gamo and Ari Zones. A systematic random sampling technique was used to select 343 study participants. Descriptive statistics were used to describe variables. Binary logistic regression was used to identify factors associated with depression. Variables with p-value <0.25 on the bivariable logistic regression analysis were candidates for the multivariable logistic regression analysis. Adjusted odds ratio (AOR) with a corresponding 95% confidence interval (CI) was used to determine the strength of association. A p-value <0.05 was used to set a statistical significance. Result A total of 343 HIV-positive youths were included in the study, with a 96.4% response rate. The proportion of depression was 22.2% (95%CI: 18.1%, 26.9%). Poor psychosocial support (AOR = 2.87; 95%CI: 1.18, 6.98), death of parents (AOR = 3.28; 95%CI: 1.73, 6.20), substance use (AOR = 3.44; 95%CI: 1.60, 7.43), advanced WHO clinical staging (AOR = 4.35; 95% CI: 1.97, 9.61), and initiation on a non-Dolutegravir (DTG)-based regimen (AOR = 2.72; 95%CI: 1.15, 6.42) were associated with depression among HIV positive youths. Conclusion Depression is found to be a significant public health problem in the study settings. Poor psychosocial support, death of parents, substance use, advanced WHO clinical staging, and initiation on a non-DTG-based regimen were significant predictors of depression. Special attention should be given to those with poor psychosocial support, substance use, orphaned, and poor baseline clinical characteristics. Moreover, early identification and treatment of youths with depression during routine HIV care is essential to avert depression.